Limits to Growth and the Quality of Life in Oxnard, California - Dagodag, Tim; Schollinger, John; Maida, Carl (The Sustainability Council of Ventura County)
A cooperative effort between the Urban Studies and Planning Program and the Department of Health Sciences of California State University, Northridge and the Sustainability Council of Ventura County